2021
DOI: 10.1111/fcre.12552
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Components of Infertility

Abstract: Infertility is a medical diagnosis impacting 48.5 million couples globally. Infertility impacts physical and emotional health as well as social and romantic relationships. People with infertility report feelings of distress, grief, anxiety and depression. Couples notice changes in their relationships; some report becoming emotionally closer while others report relationship difficulties. People may feel more isolated due to lack of social support. People that use third party reproduction, such as donor egg, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Our results also indicated that the perceived impact of infertility was significantly higher in the intrapersonal than in the interpersonal domain, as also reported in the IRSS original validation study ( Casu and Gremigni, 2016 ) and coherent with previous evidence that the stressful implications of infertility concern the domain of self, more than social life ( Karabulut et al, 2013 ; Swanson and Braverman, 2021 ). In this study, the difference between levels of infertility-related stress in the two life domains was moderate for a duration of infertility of 1–2 years and small for more than 2 years of infertility duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also indicated that the perceived impact of infertility was significantly higher in the intrapersonal than in the interpersonal domain, as also reported in the IRSS original validation study ( Casu and Gremigni, 2016 ) and coherent with previous evidence that the stressful implications of infertility concern the domain of self, more than social life ( Karabulut et al, 2013 ; Swanson and Braverman, 2021 ). In this study, the difference between levels of infertility-related stress in the two life domains was moderate for a duration of infertility of 1–2 years and small for more than 2 years of infertility duration.…”
Section: Discussionsupporting
confidence: 92%
“…Stress can affect immune system activity and thus lead to physical and mental vulnerability ( Segerstrom and Miller, 2004 ). Implications of infertility include physical symptoms, reduced psychological well-being and quality of life, feelings of guilt and shame, use of negative avoidance coping strategies, and social isolation ( Rockliff et al, 2014 ; Luk and Loke, 2015 ; Rooney and Domar, 2016 ; Swanson and Braverman, 2021 ). Recently, a prevalence of 21–52% has been reported for depressive symptoms among infertile women, which is well above rates in the general population ( Kiani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported experiences of emotionally challenging infertility treatment are consistent with previous study findings [ 21 , 22 ]. A qualitative study conducted in Ghana to explore the experiences of women seeking ARTs found that women were anxious, stressed, and frustrated [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…The experience of infertility has been described as a form of loss, frequently resulting in feelings of grief in both women and men ( Greil et al, 2010 ; Swanson & Braverman, 2021 ; Thorn, 2009 ). There are gender-specific variations in how men and women cope with emotional distress and loss.…”
Section: Introductionmentioning
confidence: 99%